2003
DOI: 10.1167/iovs.02-1322
|View full text |Cite
|
Sign up to set email alerts
|

Human Lens Thioredoxin: Molecular Cloning and Functional Characterization

Abstract: The upregulation of Trx1 in HLE B3 cells under oxidative stress and the presence of Trx1 in the lens suggest that the thioredoxin system may be an effective defense system that protects the lens against oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
1
23
1
Order By: Relevance
“…In each case, oxidative stress transiently up-regulated TRx as we have previously observed (Yegorova et al, 2003,Moon et al, 2004. It is reasonable to expect that cells under oxidative stress would require more TRx as an antioxidant to combat oxidative stress, or as an oxidation damage repair system to maintain redox homeostasis.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In each case, oxidative stress transiently up-regulated TRx as we have previously observed (Yegorova et al, 2003,Moon et al, 2004. It is reasonable to expect that cells under oxidative stress would require more TRx as an antioxidant to combat oxidative stress, or as an oxidation damage repair system to maintain redox homeostasis.…”
Section: Discussionsupporting
confidence: 79%
“…Such treatment showed no effect on the mitochondrial isoform of TRx (TRx-2) (Bhuyan et al, 2002). Our laboratory has shown that exposure of human lens epithelial (HLE-B3) cells to H 2 O 2 caused a transient up-regulation of TRx gene, corroborating the transient increase in enzyme activity and protein level (Yegorova et al, 2003). A similar result in transient TRx-1 up-regulation was found in the epithelium of cultured porcine lenses exposed to H 2 O 2 (Moon et al, 2004).…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations